2021
DOI: 10.1111/adb.13050
|View full text |Cite
|
Sign up to set email alerts
|

More than just statics: Temporal dynamic changes of intrinsic brain activity in cigarette smoking

Abstract: Smoking is companied with altered intrinsic activity of the brain measured by amplitude of low‐frequency fluctuation. Evidence has revealed that human brain activity is a highly dynamic and rapidly changing system. How exactly cigarette smoking affect temporal dynamic intrinsic brain activity is not fully understood nor is it clear how smoking severity influences spontaneous brain activity. Dynamic amplitude of low‐frequency fluctuation (dALFF) was used to examine the dynamic temporal variability in 93 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Besides, the superior frontal gyrus was considered as a possible target of neuromodulation in overweight/obesity for it can significantly predicted BMI ( 44 , 45 ). Similarly, in heavy smokers, spontaneous activity in the superior frontal gyrus was also affected by chronic tobacco intaking ( 15 ). Combined, we infer that the superior frontal gyrus is the shared neurobiological substrate in tobacco addiction and overweight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the superior frontal gyrus was considered as a possible target of neuromodulation in overweight/obesity for it can significantly predicted BMI ( 44 , 45 ). Similarly, in heavy smokers, spontaneous activity in the superior frontal gyrus was also affected by chronic tobacco intaking ( 15 ). Combined, we infer that the superior frontal gyrus is the shared neurobiological substrate in tobacco addiction and overweight.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on smoking cessation suggested that repeated tobacco exposure could “hijack” natural reward circuitry by increasing the desire to obtain tobacco, and smoking cessation would restore striatal resting-state functional connectivity ( 13 , 14 ). Moreover, serious tobacco addiction could affect brain regional spontaneous activity in the higher functional cortex, such as the superior frontal gyrus and precentral gyrus ( 15 ). Combined, the reward circuit and executive control system play an important role in the development of tobacco addiction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, while the findings of the present study advance our neuroscientific understanding of the functional anatomy of déjà vu, further research is needed to explore other factors that might influence experiences of the phenomenon through their known effects on brain function. The present study did not attempt to match individuals reporting DV and those who did not on body mass index and cigarette smoking, for example, which have been shown to impact upon fractional amplitude of low‐frequency fluctuation in several brain regions (Chao et al, 2018; Wen et al, 2021). Future research should examine the influence of such factors on the frequency of DV experience, thereby facilitating more accurate neuropsychological models of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Continuously, the initial voluntary action could turn into a chronic, relapsing mental disorder characterized by compulsive tobacco seeking and smoking 8 . Such transition has been suggested that associated with a functional shift in subregions of striatum: Exaggerated responses of the ventral striatal reward system engaged in excessive substance using at an early stage, while dorsal part dominated after the formation of compulsive behaviours 9,10 . Although the VTA and striatum played an important role in describing the reaction‐related features of tobacco addiction, results from recent neuroimaging studies have implicated the additional brain regions, especially the prefrontal cortex (PFC) 10,11 .…”
Section: Introductionmentioning
confidence: 99%